Brilliant. Vol. 1 - Bendis, Brian Michael; Bagley, Mark (2014)
Brilliant tells the story of a handful of college-age geniuses who challenge each other to solve the mystery of superpowers. Can the best and brightest change science fiction into science fact? And if so, how will the world at large react? Brilliant is a thriller of the highest order. It is the story of how true power can either destroy or protect the strongest of friendships. It is the story of how the world will react when our true potential is finally unlocked!
"Contains material originally published in magazine form as Brilliant #1-5".
Keywords: Science -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Gifted persons -- Comic books, strips, etc; Superhero comic books, strips, etc; Science fiction comic books, strips, etc; Graphic novels